STUDY BETWEEN INTERIOR COLOURS AND MEMORIES IN ARCHITECTURAL STUDIO-BASED CLASSROOM - Hidayat, Robi; Saefulloh, Asep; Maulana, Ikbal; Wardhani, Mustika Kusumaning (Jurnal Arsitektur GRID, 2024)
The colour of a room creates a particular atmosphere, one of which is creating memories for the user. The final project studio space is a meaningful space for final architecture students. The role of human sensors, such as the sense of sight, can respond to and record visible things, such as colours and shapes, which are then stored in the brain's memory. This research aims to observe the influence of interior colours, which can influence final project student productivity, and also the possibility of the emergence of memory factors that occur. The method used in this research is a qualitative research method involving an artificial intelligence program to capture a picture of space that matches the response of space users. It is hoped that the results of this research will be a novelty for the study of architectural psychology, especially in architectural studio spaces. The results of the research that has been carried out show that colour combinations and colour preferences influence the level of productivity of final project students and the memories that are formed while using the space.